2019
DOI: 10.1021/acsami.9b11453
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Switchable Polymeric Coating Kills Bacteria and Prevents Biofilm Formation in Vivo

Abstract: Preventing bacterial biofilm formation on medical devices and implants in vivo still remains a daunting task. Current antibacterial coatings to combat implant-associated infections are generally composed of toxic metals or nondegradable polymers and involve multistep surface modifications. Here, we present a charge-switchable antibacterial and antibiofilm coating based on water-insoluble cationic hydrophobic polymers that are soluble in organic solvents and can be noncovalently coated onto different surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 58 publications
0
51
0
Order By: Relevance
“…In contrast, ionic liquids mainly disrupt the bacterial membrane by interacting and creating pores, cell leakage and death occur with their rapid action [85]. These membrane alterations, which lead to bacterial death, can be traced by the effect of ionic liquids on membrane properties.…”
Section: Demeritsmentioning
confidence: 99%
“…In contrast, ionic liquids mainly disrupt the bacterial membrane by interacting and creating pores, cell leakage and death occur with their rapid action [85]. These membrane alterations, which lead to bacterial death, can be traced by the effect of ionic liquids on membrane properties.…”
Section: Demeritsmentioning
confidence: 99%
“…And this strong diffuse barrier hinders the penetration of antibiotics, especially positively charged ones [5,6], greatly improving the viability of bacteria [7]. The current studies found that P.a can use Quorum Sensing (QS) systems to regulate toxic factor formation named Las system (lasI/lasR) [8].…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19] In another approach, researchers have developed an alternative method to coat surfaces through physical deposition or non-covalent attachment of cationic polymers. [20][21][22][23][24][25] Our group has reported the development of an organo-soluble, hydrophobic, quaternary polyethyleneimine (PEI)-based antimicrobial paint. In a prototype study, these polymers were coated on glass slides and their antibacterial and antifungal activities were evaluated.…”
Section: Introductionmentioning
confidence: 99%